O desenvolvimento como direito humano fundamental à luz do direito constitucional econômico - Barbosa, Iuri Gnatiuc (2020)
The present work intends to analyze the way in which the development and protection of Human Rights are related, in order to verify if the rule provided for in article 170 of the Federal Constitution is effective to guarantee economic development in a sustainable manner. A change in the economic scenario is perceived, with the passage of capital as a characteristic element of private power and no longer of the State, as in other historical moments. It analyzed the mandatory protection of Human Rights, also, by the business community considering the economic power that was transferred to their ownership, concluding with the perception of the need for action of this agent for protectionist purposes and that guarantee development.